A Macrofinancial Approach to Supervisory Standards Assessments. (Policy Papers; Policy Paper ;, 2014)
Standards assessments serve several important objectives but are not well integrated into Fund surveillance. Financial standards assessments, when undertaken in the context of FSAPs, are used to identify weaknesses in financial regulation and supervision, or other areas covered by international standards. However, those weaknesses are not specifically linked to the risks and vulnerabilities facing the financial sector. Conversely, the analysis of country-specific vulnerabilities in the FSAP does not contribute to targeting the standard assessment effort, since the assessment must be exhaustive and cover the entire standard.